A simplified herbal decoction attenuates myocardial infarction by regulating macrophage metabolic reprogramming and phenotypic differentiation via modulation of the HIF-1α/PDK1 axis - Zhi-jun Lin; Xin Dong; Huan He; Jia-lin Jiang; Zhuo-ji Guan; Xuan Li; Lu Lu; Huan Li; Yu-sheng Huang; Shao-xiang Xian; Zhong-qi Yang; Zi-xin Chen; et al. (BMC, 2024)
Abstract Background Myocardial infarction (MI) poses a global public health challenge, often associated with elevated mortality rates and a grim prognosis. A crucial aspect of the inflammatory injury and healing process post-MI involves the dynamic differentiation of macrophages. A promising strategy to alleviate myocardial damage after MI is by modulating the inflammatory response and orchestrating the shift from pro-inflammatory (M1) to anti-inflammatory (M2) macrophages, aiming to achieve a reduced M1/M2 ratio. Nuanxinkang (NXK), a simplified herbal decoction, has demonstrated noteworthy cardioprotective, inflammation-regulating, and myocardial energy metabolism-regulating properties. Methods In this study, we constructed an MI model by ligating coronary arteries to investigate the efficacy of NXK in improving ventricular remodeling and cardiac function. Mice were administered NXK (1.65 g/kg/d) or an equivalent volume of regular saline via gavage for 28 consecutive days, commencing the day after surgery. Then, we conducted echocardiography to assess the cardiac function, Masson staining to illustrate the extent of myocardial fibrosis, TUNEL staining to reveal myocardial apoptosis, and flow cytometry to analyze the polarization of M1 and M2 macrophages in the hearts. Besides, a lipopolysaccharide (LPS)-induced pro-inflammatory macrophage (M1) polarization model was implemented in RAW264.7 cells to elucidate the underlying mechanism of NXK in regulating macrophage polarization. RAW264.7 cells were pre-treated with or without NXK-containing serum. Oxidative stress was detected by MitoSox staining, followed by Seahorse energy metabolism assay to evaluate alterations in mitochondrial metabolic patterns and ATP production. Both In vivo and in vitro, HIF-1α and PDK1 were detected by fluorescent quantitative PCR and Western blotting. Results In vivo, MI mice exhibited a decline in cardiac function, adverse ventricular remodeling, and an increase in glycolysis, coupled with M1-dominant polarization mediated by the HIF-1α/PDK1 axis. Notably, robust responses were evident with high-dose NXK treatment (1.65 g/kg/day), leading to a significant enhancement in cardiac function, inhibition of cardiac remodeling, and partial suppression of macrophage glycolysis and the inflammatory phenotype in MI mice. This effect was achieved through the modulation of the HIF-1α/PDK1 axis. In vitro, elevated levels of mitochondrial ROS production and glycolysis were observed in LPS-induced macrophages. Conversely, treatment with NXK notably reduced the oxidative stress damage induced by LPS and enhanced oxidative phosphorylation (OXPHOS). Furthermore, NXK demonstrated the ability to modify the energy metabolism and inflammatory characteristics of macrophages by modulating the HIF-1α/PDK1 axis. The influence of NXK on this axis was partially counteracted by the HIF-1α agonist DMOG. And NXK downregulated PDK1 expression, curtailed glycolysis, and reversed LPS-induced M1 polarization in macrophages, similar to the PDK1 inhibitor DCA. Conclusion In conclusion, NXK protects against MI-induced cardiac remodeling by inducing metabolic reprogramming and phenotypic differentiation of macrophages, achieved through the modulation of the HIF-1α/PDK1 axis. This provides a novel and promising strategy for the treatment of MI.